Comparative study of serum bilirubin and total leukocyte count in assessing the severity of acute appendicitis - Shahi , Dinesh; Menyangbo, Suryaman; Verma, Atmanand; Neupane , Ananda; Khaniya , Sushil (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Appendicitis is diagnosed based on the combination of clinical assessment, laboratory investigation, and radiological test. Distinguishing between uncomplicated and complicated appendicitis remains a frequent challenge in clinical practice. This study is designed to evaluate and compare the diagnostic utility of serum bilirubin (TB) and total leucocyte count (TLC) in severity of appendicitis. Methods: This is a retrospective cross sectional analytical study with a sample size of 167 undergoing open appendectomy from January 2025 to January 2026 Preoperatively TLC with TB was done. Severity of appendicitis was divided in uncomplicated and complicated. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy were calculated. The optimal cut off value for each parameter and area under the curve calculated using ROC curve. Results: A total of 167 patients were included, with mean age± SD was 34.38 ± 17.80 years ,most common age group10-20 years. The sensitivity, specificity, PPV, NPV and accuracy of TLC with cut off value >11000 were 64.28%, 32.99%, 40.90%, 56.14% and 46.10%, for TB with cut off value >1.4mg/dl were 41.42%, 68.04%, 48.33%, 61.68% and 56.88%. The area under the curve (AUC) of TLC, TB and N/L ratio were 0.601, 0.573 and 0.745. The diagnostic accuracy of TB over TLC is statistically significant (p value <0.001). Conclusion: Increased bilirubin level has higher diagnostic accuracy than leukocytosis for severity of appendicitis. Combining inflammatory biomarkers such as TLC and TB improves diagnostic accuracy in appendic